The complete chloroplast genome sequence of Ficus beipeiensis (Moraceae), an endemic and endangered plant in China - Han, Fang (Mitochondrial DNA B Resour, 2021)
Ficus beipeiensis S.S.Chang is an evergreen plant of Ficus from the family Moraceae. This is an endangered species endemic to China. In terms of economic value, F. beipeiensis are used as a native plant resource of urban landscaping in Chongqing, China. Here, we sequenced, assembled and annotated the chloroplast (cp) genome of F. beipeiensis, and aim to provide genetic resources for this endangered species. The length of cp genome was 160,595 bp, with a large single-copy region (LSC) of 88,683 bp and a small single-copy region (SSC) of 20,160 bp separated by a pair of inverted repeats (IRs) of 25,876 bp. It encodes 110 unique genes, including 76 protein-coding genes, 30 transfer RNA genes, and 4 ribosomal RNA genes. Besides, we reconstructed the phylogeny of Moraceae based on the whole cp genome sequences data set. Phylogenetic analysis shows that all analyzed Ficus species are clustered and form a monophyletic group. Antiaris is a sister group to Ficus. In our maximum likelihood (ML) tree, F. beipeiensis is closely related to F. racemose.